2008
DOI: 10.1038/nrn2532
|View full text |Cite
|
Sign up to set email alerts
|

A cortical network for semantics: (de)constructing the N400

Abstract: Measuring event-related potentials (ERPs) has been fundamental to our understanding of how language is encoded in the brain. One particular ERP response, the N400 response, has been especially influential as an index of lexical and semantic processing. However, there remains a lack of consensus on the interpretation of this component. Resolving this issue has important consequences for neural models of language comprehension. Here we show that evidence bearing on where the N400 response is generated provides k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

137
1,290
11
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,430 publications
(1,446 citation statements)
references
References 183 publications
137
1,290
11
8
Order By: Relevance
“…By contrast, the two ROIs in early visual areas showed little connectivity with higher-order processing areas but were mainly connected with adjacent visual areas (ROI1), and the left superior parietal lobule (ROI2), the latter suggesting involvement of visuospatial analysis and attention (Kanwisher and Wojciulik, 2000). Furthermore, the two most anterior ROIs (ROI4 and ROI5) did not show interlobar connections but instead were connected with the left insula (for ROI4) and the left middle temporal gyrus (for ROI5), suggesting a link to auditory phonological or modality independent lexicalsemantic processing (Lau et al, 2008;Vigneau et al, 2006). These results indicate that − within the ventral VWF-System − the VWFA may be the only brain region that is consistently functionally connected to higher-order regions of the language network, which is in agreement with the belief that the left fusiform gyrus functions as a major relay of visual stimuli into the network, considering that it encodes a wide variety of complex visual percepts, including both verbal and nonverbal stimuli (Cohen et al, 2000;Haxby et al, 2001;Kanwisher et al, 1997).…”
Section: Accepted M Manuscriptmentioning
confidence: 97%
“…By contrast, the two ROIs in early visual areas showed little connectivity with higher-order processing areas but were mainly connected with adjacent visual areas (ROI1), and the left superior parietal lobule (ROI2), the latter suggesting involvement of visuospatial analysis and attention (Kanwisher and Wojciulik, 2000). Furthermore, the two most anterior ROIs (ROI4 and ROI5) did not show interlobar connections but instead were connected with the left insula (for ROI4) and the left middle temporal gyrus (for ROI5), suggesting a link to auditory phonological or modality independent lexicalsemantic processing (Lau et al, 2008;Vigneau et al, 2006). These results indicate that − within the ventral VWF-System − the VWFA may be the only brain region that is consistently functionally connected to higher-order regions of the language network, which is in agreement with the belief that the left fusiform gyrus functions as a major relay of visual stimuli into the network, considering that it encodes a wide variety of complex visual percepts, including both verbal and nonverbal stimuli (Cohen et al, 2000;Haxby et al, 2001;Kanwisher et al, 1997).…”
Section: Accepted M Manuscriptmentioning
confidence: 97%
“…Damian and Als (2005) proposed that the blocked cyclic naming paradigm might involve contributions from two separate mechanisms: a short-lived semantic priming effect in the first presentation cycle and a longer-lasting interference effect emerging with repetition in subsequent cycles (e.g., Wheeldon & Monsell, 1994; see also Navarrete et al, 2012). Semantic priming effects are observed reliably in LIFG (see Badre & Wagner, 2004;Lau, Phillips, & Poeppel, 2008 for reviews). Hence, this confound might explain the LIFG results reported in some studies of blocked cyclic naming.…”
Section: Neuroanatomical Correlates Of Mechanisms Proposed To Accountmentioning
confidence: 99%
“…Considering that the N400 is particularly sensitive to semantic processes (for reviews see Kutas & Federmeier, 2011;Kutas & Van Petten, 1994;Kutas, Van Petten, & Kluender, 2006; see also Lau, Phillips, & Poeppel, 2008), these findings suggest that context effects in word recognition may well depend on presentation rate.…”
Section: The Role Of Presentation Ratementioning
confidence: 99%
“…Given its relatively late appearance in the time course, the N400 was sometimes considered as a pure indicator of post-lexical processing (e.g., Holcomb, 1993;Misra & Holcomb, 2003). However, other reports pointed to its sensitivity to lexical operations (e.g., Deacon, Dynowska, Ritter, & Grose-Fifer, 2004;Deacon, Hewitt, Yang, & Nagata, 2000; see also Lau et al, 2008;Van Petten, 1995) and demonstrated joint effects of frequency and sentential context (Dambacher et al, 2006;Van Petten & Kutas, 1990). In fact, accumulating evidence from numerous N400 studies suggests that a modular classification of word-and sentencelevel information into lexical and post-lexical processes is no longer sustainable for the understanding of word recognition.…”
Section: Predictability: Top-down Expectationsmentioning
confidence: 99%